PROFIL PENGGUNAAN OBAT JANTUNG PADA PASIEN RAWAT JALAN DI RUMAH SAKIT STELLA MARIS MAKASSAR - Muhammad Tahir (Akademi Farmasi Yamasi Makassar, 2022)
Cardiovascular disease is a non-communicable disease that most often causes death, this study aims to describe the use of cardiac drugs in outpatients at the Stella Maris Hospital Makassar. The type of research conducted is descriptive through data collection which is carried out by observation, the population is all prescriptions for outpatient heart disease patients at the Stella Maris Hospital Makassar in January-March 2021. Data collection is done by looking at the medical records and prescriptions of heart disease patients. which is secondary data. The conclusion of this study is that cardiovascular patients at the Stella Maris Hospital in Makassar used amlodipine more in January-March 2021 with an average percentage of 32.7%, Bisoprolol 25.8%, Candesartan 21.9%, Furosemide 13.3 %, Simvastatin 6.87%, then Nifedipine 1.25% and the least used drug Captopril 0.13%. There are more patients with heart disease in men (50.2%) than women (42.6%) in January-March 2021. Patients with heart disease at the Stella Maris Hospital Makassar are more with an age range of >60-85 years (89%) than patients with an age range of 35-60 years (11%).